Choosing a substrate for the ion irradiation of two-dimensional materials - Kolesov, Egor A. (Beilstein Journal of Nanotechnology, 2019)
This study is dedicated to the common problem of how to choose a suitable substrate for ion irradiation of two-dimensional materials in order to achieve specific roles of certain defect formation mechanisms. The estimations include Monte Carlo simulations for He, Ar, Xe, C, N and Si ions, performed in the incident ion energy range from 100 eV to 250 MeV. Cu, SiO2, SiC and Al2O3 substrates were analyzed. The considered substrate-related defect formation mechanisms are sputtering, recoil atoms reaching the interface with a non-zero energy, and generation of hot electrons in close proximity of the interface. Additionally, the implantation of sputtered substrate atoms into the 2D material lattice is analyzed. This work is useful both for fundamental studies of irradiation of two-dimensional materials and as a practical guide on choosing the conditions necessary to obtain certain parameters of irradiated materials.
Keywords: 2D materials; defects; hot electrons; ion irradiation; recoils; sputtering; substrate

(untitled) - Zhao, S.; Xue, J.; Wang, Y.; Yan, S. (Nanotechnology, 2012)

(untitled) - Madauß, L.; Ochedowski, O.; Lebius, H.; Ban-d’Etat, B.; Naylor, C. H.; Johnson, A. T. C.; Kotakoski, J.; Schleberger, M. (2D Mater., 2016)

(untitled) - Mathew, S.; Chan, T. K.; Zhan, D.; Gopinadhan, K.; Barman, A.-R.; Breese, M. B. H.; Dhar, S.; Shen, Z. X.; Venkatesan, T.; Thong, J. T. L. (Carbon, 2011)

(untitled) - Kretschmer, S.; Maslov, M.; Ghaderzadeh, S.; Ghorbani-Asl, M.; Hlawacek, G.; Krasheninnikov, A. V. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Compagnini, G.; Giannazzo, F.; Sonde, S.; Raineri, V.; Rimini, E. (Carbon, 2009)

(untitled) - Mathew, S.; Chan, T. K.; Zhan, D.; Gopinadhan, K.; Roy Barman, A.; Breese, M. B. H.; Dhar, S.; Shen, Z. X.; Venkatesan, T.; Thong, J. T. L. (J. Appl. Phys., 2011)

(untitled) - Li, W.; Wang, X.; Zhang, X.; Zhao, S.; Duan, H.; Xue, J. (Sci. Rep., 2015)

(untitled) - Herbig, C.; Åhlgren, E. H.; Jolie, W.; Busse, C.; Kotakoski, J.; Krasheninnikov, A. V.; Michely, T. (ACS Nano, 2014)

(untitled) - Davydov, S. Y. (Tech. Phys. Lett., 2011)

(untitled) - Li, Y.; Qi, Z.; Liu, M.; Wang, Y.; Cheng, X.; Zhang, G.; Sheng, L. (Nanoscale, 2014)

(untitled) - Kong, L.; Bjelkevig, C.; Gaddam, S.; Zhou, M.; Lee, Y. H.; Han, G. H.; Jeong, H. K.; Wu, N.; Zhang, Z.; Xiao, J.; Dowben, P. A.; Kelber, J. A. (J. Phys. Chem. C, 2010)

(untitled) - Romero, H. E.; Shen, N.; Joshi, P.; Gutierrez, H. R.; Tadigadapa, S. A.; Sofo, J. O.; Eklund, P. C. (ACS Nano, 2008)

(untitled) - Krasheninnikov, A. V.; Miyamoto, Y.; Tománek, D. (Phys. Rev. Lett., 2007)

(untitled) - Lenner, M.; Kaplan, A.; Huchon, C.; Palmer, R. E. (Phys. Rev. B, 2009)

(untitled) - Krasheninnikov, A. V.; Nordlund, K. (J. Appl. Phys., 2010)

(untitled) - Kolesov, E. A.; Tivanov, M. S.; Korolik, O. V.; Apel, P. Y.; Skuratov, V. A.; Saad, A.; Komissarov, I. V. (J. Mater. Sci.: Mater. Electron., 2018)

Ion–solid Interactions - Nastasi, M.; Mayer, J.; Hirvonen, J. K. (Cambridge University Press, 1996)

(untitled) - Ghorbani-Asl, M.; Kretschmer, S.; Spearot, D. E.; Krasheninnikov, A. V. (2D Mater., 2017)

(untitled) - Komsa, H.-P.; Kotakoski, J.; Kurasch, S.; Lehtinen, O.; Kaiser, U.; Krasheninnikov, A. V. (Phys. Rev. Lett., 2012)

(untitled) - Merrill, A.; Cress, C. D.; Rossi, J. E.; Cox, N. D.; Landi, B. J. (Phys. Rev. B, 2015)

(untitled) - Skowron, S. T.; Lebedeva, I. V.; Popov, A. M.; Bichoutskaia, E. (Chem. Soc. Rev., 2015)

(untitled) - McKenna, A. J.; Trevethan, T.; Latham, C. D.; Young, P. J.; Heggie, M. I. (Carbon, 2016)

(untitled) - Lin, Z.; Carvalho, B. R.; Kahn, E.; Lv, R.; Rao, R.; Terrones, H.; Pimenta, M. A.; Terrones, M. (2D Mater., 2016)

(untitled) - Wadey, J. D.; Markevich, A.; Robertson, A.; Warner, J.; Kirkland, A.; Besley, E. (Chem. Phys. Lett., 2016)

(untitled) - Bangert, U.; Pierce, W.; Kepaptsoglou, D. M.; Ramasse, Q.; Zan, R.; Gass, M. H.; Van den Berg, J. A.; Boothroyd, C. B.; Amani, J.; Hofsäss, H. (Nano Lett., 2013)

(untitled) - Li, W.; Xue, J. (RSC Adv., 2015)

(untitled) - Cress, C. D.; Schmucker, S. W.; Friedman, A. L.; Dev, P.; Culbertson, J. C.; Lyding, J. W.; Robinson, J. T. (ACS Nano, 2016)

(untitled) - Murray, R.; Haynes, K.; Zhao, X.; Perry, S.; Hatem, C.; Jones, K. (ECS J. Solid State Sci. Technol., 2016)

(untitled) - Åhlgren, E. H.; Kotakoski, J.; Krasheninnikov, A. V. (Phys. Rev. B, 2011)

(untitled) - Agius Anastasi, A.; Valsesia, A.; Colpo, P.; Borg, M. K.; Cassar, G. (Diamond Relat. Mater., 2018)

(untitled) - Maguire, P.; Fox, D. S.; Zhou, Y.; Wang, Q.; O'Brien, M.; Jadwiszczak, J.; Cullen, C. P.; McManus, J.; Bateman, S.; McEvoy, N.; Duesberg, G. S.; Zhang, H. (Phys. Rev. B, 2018)

(untitled) - Da, B.; Shinotsuka, H.; Yoshikawa, H.; Ding, Z. J.; Tanuma, S. (Phys. Rev. Lett., 2014)

(untitled) - Garmash, V. I.; Djuzhev, N. A.; Kirilenko, E. P.; Makhiboroda, M. A.; Migunov, D. M. (J. Surf. Invest.: X-Ray, Synchrotron Neutron Tech., 2016)

(untitled) - Ochedowski, O.; Marinov, K.; Wilbs, G.; Keller, G.; Scheuschner, N.; Severin, D.; Bender, M.; Maultzsch, J.; Tegude, F. J.; Schleberger, M. (J. Appl. Phys., 2013)

(untitled) - Ziegler, J. F.; Ziegler, M. D.; Biersack, J. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)